Les accidents de la route dans les médias de masse en Algérie - Houria Bencherif; Farès Boubakour; Naima Belkacem (Communication)
This research brief presents a content analysis of a sample of Algerian mass media’s coverage of road accidents in 2008. The written press’s coverage is judged as barely adequate while radio all but ignores the subject. Only television pays any attention and allots the necessary resources. These failings are due to the absence of a national policy and strategy for the prevention of road accidents.